The prevalence and psychosocial correlates of ketum use among individuals on methadone maintenance therapy programme in Hospital Taiping / Choo, Ling Ling - Choo, Ling Ling (2022)
Background: Ketum use is significantly prevalent amongst individuals in northern states of Peninsular Malaysia. This study aims to investigate the prevalence and psychosocial correlates of Ketum use in individuals who are in the Methadone Maintenance Therapy (MMT) Programme in Hospital Taiping. Methods: This is a cross-sectional study conducted in the methadone clinic Hospital Taiping. Non-probability convenience sampling was used in this study. The study instruments used were Subjective Opiate Withdrawal Scale (SOWS), Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) questionnaire, and Kratom Dependence Scale (KDS). Results: A total of 215 subjects were recruited in this study. The prevalence of ketum users was 49.3% (n=106). The factors which were significantly associated with ketum use (p < 0.05) in MMT programme were ethnicity, duration in MMT programme, other illicit drugs use, and SOWS. Conclusion: Ketum use is prevalent amongst those in MMT programme in this study. The high prevalence of ketum use is of concern and further interventions should be carried out to address this